Systematic monitoring for detection of atrial fibrillation in patients with acute ischaemic stroke (MonDAFIS): a randomised, open-label, multicentre study. Issue 6 (June 2021) - Haeusler, Karl Georg; Kirchhof, Paulus; Kunze, Claudia; Tütüncü, Serdar; Fiessler, Cornelia; Malsch, Carolin; Olma, Manuel C; Jawad-Ul-Qamar, Muhammad; Krämer, Michael; Wachter, Rolf; Michalski, Dominik; Kraft, Andrea; et al.
Summary: Background: Systematic electrocardiogram (ECG) monitoring improves detection of covert atrial fibrillation in stroke survivors but the effect on secondary prevention is unknown. We aimed to assess the effect of systematic ECG monitoring of patients in hospital on the rate of oral anticoagulant use after 12 months. Methods: In this investigator-initiated, randomised, open-label, parallel-group multicentre study with masked endpoint adjudication, we recruited patients aged at least 18 years with acute ischaemic stroke or transient ischaemic attack without known atrial fibrillation in 38 certified stroke units in Germany. Patients were randomly assigned (1:1) to usual diagnostic procedures for atrial fibrillation detection (control group) or additional Holter-ECG recording for up to 7 days in hospital (intervention group). Patients were stratified by centre using a random permuted block design. The primary outcome was the proportion of patients on oral anticoagulants at 12 months after the index event in the intention-to-treat population. Secondary outcomes included the number of patients with newly diagnosed atrial fibrillation in hospital and the composite of recurrent stroke, major bleeding, myocardial infarction, or death after 6 months, 12 months, and 24 months. This trial was registered with ClinicalTrials.gov, NCT02204267, and is completed and closed for participants. Findings: Between Dec 9, 2014, and Sept 11, 2017, 3465 patients were randomly assigned, 1735 (50·1%) to the intervention group and 1730 (49·9%) to the control group. Oral anticoagulation status was available in 2920 (84·3%) patients at 12 months (1484 [50·8%] in the intervention group and 1436 [49·2%] in the control group). For the primary outcome, at 12 months, 203 (13·7%) of 1484 patients in the intervention group versus 169 (11·8%) of 1436 in the control group were on oral anticoagulants (odds ratio [OR] 1·2 [95% CI 0·9–1·5]; p=0·13). Atrial fibrillation was newly detected in patients in hospital in 97 (5·8%) of 1714 in the intervention group versus 68 (4·0%) of 1717 in the control group (hazard ratio [HR] 1·4 [95% CI 1·0–2·0]; p=0·024). The composite of cardiovascular outcomes and death did not differ between patients randomly assigned to the intervention group versus the control group at 24 months (232 [13·5%] of 1714 vs 249 [14·5%] of 1717; HR 0·9 [0·8–1·1]; p=0·43). Skin reactions due to study ECG electrodes were reported in 56 (3·3%) patients in the intervention group. All-cause death occured in 73 (4·3%) patients in the intervention group and in 103 (6·0%) patients in the control group (OR 0·7 [0·5–0·9]). Interpretation: Systematic core centrally reviewed ECG monitoring is feasible and increases the detection rate of atrial fibrillation in unselected patients hospitalised with acute ischaemic stroke or transient ischaemic attack, if added to usual diagnostic care in certified German stroke units. However, we found no effect of systematic ECG monitoring on the rate of oral anticoagulant use after 12 months and further efforts are needed to improve secondary stroke prevention. Funding: Bayer Vital. Translation: For the German translation of the abstract see Supplementary Materials section.